2014
DOI: 10.1016/j.physa.2014.08.021
|View full text |Cite
|
Sign up to set email alerts
|

One-way-ness in the input-saving (Turing) machine

Abstract: h i g h l i g h t s• We use an information heat engine to physically create a permutation operation.• The mechanism relies on Bennett's algorithm of the reversible Turing machine. • Reversion of the algorithm provoked erasure of information with gain of entropy.• Erasure with gain of entropy causes a one-way (permutation) quantum gate.• We showed that a cascade of two C-NOT gates in an adiabatic constraint is one-way. a b s t r a c tCurrently, a complexity-class problem is proving the existence of one-way perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It is straightforward to see that strongly non-invertible functions are invertible from the definition itself of one-way functions. (See a thermodynamic approach of one wayness [32] in input-saving machines [33,34]).…”
Section: 52mentioning
confidence: 99%
“…It is straightforward to see that strongly non-invertible functions are invertible from the definition itself of one-way functions. (See a thermodynamic approach of one wayness [32] in input-saving machines [33,34]).…”
Section: 52mentioning
confidence: 99%
“…The problem that one encounters is the closing of the cycle. An approach to solve this problem has been proposed in [159]. The approach one can think of is by moving the partition wall to the extreme right of the chamber as shown in Fig.…”
Section: Origin Of the Inverse Problemmentioning
confidence: 99%
“…The existence of one-way-ness has a great impact on the complexity class problems, as one can link this to the physical constraints rather than its mathematical limitations [32,43,44]. In the seminal work [159], they have proposed an approach to bridge a connection between the one-way permutation to thermodynamic computation. They have shown that a quantum circuit maps a target bit to itself [45].…”
mentioning
confidence: 99%